Inflammation Pharmacological Reaction and YMDD Mutational Patterns in Lamivudine Therapeutics Hepatitis B Virus - Liu, Hongcan; Wan, Zemin; She, Lanhui; Zhu, Yajuan; Cai, Zhiliang; Wu, Bin; Zhuang, Qizhen; Ke, Peifeng; Wu, Xinzhong; Li, Zhuo; Huang, Xianzhang (Frontiers in Pharmacology, 2021)
Background/Aims: Emergence of tyrosine-methionine-aspartate-aspartate (YMDD) motif in reverse transcriptase is a serious problem in chronic hepatitis B(CHB) patients after Lamivudine (LAM) therapy. However, the relationship between inflammation pharmacological reaction and YMDD mutational patterns of CHB has not been well-characterized. The aim of this study was to investigate the inflammation pharmacological reaction and different YMDD mutants patterns of CHB patients. Methods: We investigated the inflammation pharmacological reaction and YMDD mutational patterns through biochemical, serological and virological detection among 83 CHB patients, including 25 YMDD mutants, 25 under detection, and 33 control patients without YMDD mutants. Results: Prevalence of YMDD mutation patterns is different. Among 25 YMDD mutants patients, YIDD was the dominant mutation (72%), followed YVDD (16%) and the hybrid YIDD + YVDD (12%). The time course during the YMDD mutations was also different. 52.4% patients developed the mutation less than 12 months after the LAM therapy. Serum hepatitis B virus (HBV) DNA level in patients with YMDD mutants were significantly higher than that in control and negative groups. Serum HbsAg and HbeAg in patients with YMDD mutants were also higher than those in control and negative groups, despite no significant difference was found forserum HbeAb. ALT and AST levels were also significantly higher in mutants group. Conclusions: Illuminating inflammation pharmacological reaction and YMDD mutational patterns of CHB during pathological process may have implications for future therapy in YMDD mutation patients. This may have impact on the choice of treatment strategies for lamivudine-resistant HBV.